The Influence of Catcalling on the Attitude of Hijab Women in Padang City - Choiriyah (Journal of Media and Communication | E-ISSN : 3063-9581, 2024)
This research is entitled "The Influence of Catcalling on the Attitudes of Hijab-wearing Women in Tanjung Batu Village, Ogan Ilir Regency." The aim of this research is to determine the effect of catcalling on the attitudes of hijab-wearing women in Tanjung Batu Village, Ogan Ilir Regency and the factors that cause catcalling among hijab-wearing women. This research is a quantitative approach that is correlational in nature. This research uses the S-O-R theory. The subjects of this research were 23 women wearing the hijab using purposive sampling techniques from a total population of 30 women wearing the hijab. With a sampling formula using the Solvin formula and a value of e = 0.1 (10%) for large populations. The data collection technique used a Likert questionnaire which was distributed to 23 women wearing the hijab and documentation. The data analysis technique uses a one sample t-test. The results of this research show that there is no influence and no significant relationship between catcalling and the attitudes of women wearing the hijab in Tanjung Batu Village, Ogan Ilir Regency. This is based on the results of statistical hypothesis testing using the SPSS.22 program which obtained a calculated t value of t = 0.960 < 2.080 with a significance of 0.348, so Ho is accepted and Ha is rejected. This is reinforced by findings in the field where women wearing the hijab in Tanjung Batu Village do not have an in-depth understanding and knowledge of catcalling and most of the attitudes of women wearing the hijab are influenced by other variables such as personal, traumatic experiences, people who are considered important, social media, friendship, romance and etc.